A novel approach to rapidly prevent age‐related cognitive decline. Issue 2 (4th December 2013) - Adlard, Paul A.; Sedjahtera, Amelia; Gunawan, Lydia; Bray, Lisa; Hare, Dominic; Lear, Jessica; Doble, Philip; Bush, Ashley I.; Finkelstein, David I.; Cherny, Robert A.
Summary The loss of cognitive function is a pervasive and often debilitating feature of the aging process for which there are no effective therapeutics. We hypothesized that a novel metal chaperone (PBT2; Prana Biotechnology, Parkville, Victoria, Australia) would enhance cognition in aged rodents. We show here that PBT2 rapidly improves the performance of aged C57Bl/6 mice in the Morris water maze, concomitant with increases in dendritic spine density, hippocampal neuron number and markers of neurogenesis. There were also increased levels of specific glutamate receptors (alpha‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid and N‐methyl‐d‐aspartate), the glutamate transporter (VGLUT1) and glutamate itself. Markers of synaptic plasticity [calmodulin‐dependent protein kinase II (CaMKII) and phosphorylated CaMKII, CREB, synaptophysin] were also increased following PBT2 treatment. We also demonstrate that PBT2 treatment results in a subregion‐specific increase in hippocampal zinc, which is increasingly recognized as a potent neuromodulator. These data demonstrate that metal chaperones are a novel approach to the treatment of age‐related cognitive decline.